SMEs in the political struggle against TTIP. An analysis from a hegemony-theoretical perspective. - Theurl, Simon (Momentum Quarterly, 2017)
Since spring 2015 the European Commission began to argue that small and medium enterprises (SMEs) would be the real winners from TTIP and CETA. This statement is strongly combated as the economic effects of trade liberalization are ambiguous: Theoretically trade liberalization can lead to both, an increase of monopolistic competition, or an increase of variety and efficiency because of increased competition. But supporter of TTIP only put forward the possible benefits for SMEs. In this paper this is interpreted as a strategic maneuver to gain support for the implementation of the so called “deep trade agreements” TTIP and CETA. From a hegemony theoretical perspective power-relations are analyzed in this paper and it will be argued that TTIP and CETA are actually projects which reflect the interest of a “transnational block”.